The Transdisciplinary Informing Model: Bridging Epistemologies for Breakthrough Innovation - Larocca, Paulina (Informing science, 2025)
Aim/Purpose This paper addresses the need for more holistic informing frameworks that bridge cognitive-centric approaches with embodied, relational, and imaginative modes of knowledge transfer, especially within complex transdisciplinary contexts where conventional informing processes often fail to facilitate deep understanding. Background Current Informing Science frameworks primarily focus on cognitive processing and linear data flow, leaving significant gaps in understanding how knowledge can be effectively transferred through non-cognitive pathways. This paper extends Informing Science by integrating diverse epistemologies, including non-Western and phenomenological perspectives, into a cohesive visual model. Methodology Using practice-led research methodology, this study developed and tested the Transdisciplinary Informing Model (TIM) through the creation and implementation of an immersive sensory experience (Fractals of Nature). Approximately 150 participants, including art students, alumni, community members, and change-makers, engaged with three sensory stations, generating creative artifacts that were analyzed for evidence of relational knowledge creation. Contribution This paper contributes to Informing Science by visualizing and operationalizing Montuori’s principles of transdisciplinary inquiry and extending Cohen’s three-environment model to include embodied, sensory, and imaginative dimensions of knowledge transfer. The hexagonal model structure illustrates previously unseen interdependencies between principles, creating a practical framework for cross-epistemological synthesis. Findings Evidence from the Fractals of Nature case study demonstrates that TIM effectively facilitates: (1) relational knowledge creation that bridges individual perspectives with ecological awareness; (2) cross-paradigmatic synthesis across scientific, cultural, and imaginative domains; and (3) embodied knowledge processing through multisensory engagement, enabling deeper, more integrated understanding than cognitive processing alone. Recommendations for Practitioners Practitioners should consider incorporating sensory, relational, and imaginative elements into informing processes, particularly in educational, organizational, and sustainability contexts where complex, systemic understanding is essential. TIM provides a structured yet flexible framework for designing transdisciplinary experiences that engage multiple ways of knowing. Recommendations for Researchers Future research should explore TIM’s applications across diverse cultural contexts, develop metrics for evaluating its impact on knowledge transfer, and investigate the long-term effects of embodied informing approaches. Researchers should also consider combining TIM with other informing frameworks to create hybrid approaches that leverage multiple models’ strengths. Impact on Society TIM’s approach to knowledge transfer has significant implications for addressing complex societal challenges that require integrated understanding across disciplines, cultures, and knowledge systems. By fostering embodied, relational understanding of interconnectedness, TIM could enhance public engagement with systemic issues like climate change, social inequality, and technological transformation. The framework’s emphasis on ethical relationality provides a foundation for more inclusive decision-making processes that honor diverse epistemologies, potentially contributing to more equitable and sustainable social systems that bridge intellectual understanding with embodied, collective wisdom. Future Research Building on this paper’s findings, future research should: (1) investigate TIM’s effectiveness in digital and virtual environments where sensory engagement takes different forms; (2) explore applications in cross-cultural collaborations where diverse epistemologies must be bridged; (3) develop quantitative and qualitative metrics to assess the depth and retention of knowledge gained through embodied informing processes; (4) examine how TIM might enhance informing processes in complex fields like healthcare, environmental management, and technology ethics where siloed knowledge creates barriers to holistic understanding; and (5) investigate the relationship between embodied informing and behavior change, particularly in sustainability contexts where knowledge alone often fails to motivate action.